Water institutions in the Awash basin of Ethiopia: the discrepancies between rhetoric and realities. Issue 1 (2nd January 2018) - Hailu, Reta; Tolossa, Degefa; Alemu, Getnet
ABSTRACT: This paper strived to describe the features of water institutions in the Awash basin from a historical perspective based on reviews of water laws, policies, and administrative documents, as well as interviews with water actors using snowball techniques. The result revealed that institutions had rapidly been changing but not coherently built. The most centralized duties and powers of institutions, coupled with financial and technical limitations created difficulty in enforcing the laws. The policy was comprehensive and inculcated the principles of Integrated Water Resource Management. Yet, it did not properly cascade down to the lower level as it was fundamentally top-down. Several stakeholders were not involved in the policy-making process. Water institutions were overwhelmingly more rhetoric than action oriented. Customary water institutions were undermined. Therefore, critical steps need to be taken towards enforcing formal water institution, recognizing the role of customary practices, and involving the key stakeholders, and building the capacity of actors to minimize water insecurity in the basin.